Sugarcane Bagasse Biochar as a Solid Catalyst: From Literature Review of Heterogeneous Catalysts for Esterifications to the Experiments for Biodiesel Synthesis from Palm Oil Industry Waste Residue - Arif Hidayat; Winarto Kurniawan; Hirofumi Hinode (Indonesian Journal of Science and Technology, 2021)
In this study, the utilization of sugarcane bagasse biochar (SCBB) as a solid catalyst was investigated for biodiesel production from palm oil industry waste residue. The catalyst was synthesized by sulfonation of SCBB to attach sulfonate functional group. Several analyses such as Nitrogen Gas Sorption Analysis, acidity, Fourier Transform Infra-Red spectroscopy, and X-ray powder diffraction (XRD) were applied to determine the properties of SCBB catalyst. The SCBB catalysts were tested to esterify the palm oil industry waste residue which contains of Free Fatty Acids (FFAs). The SCBB catalyst activity test revealed that the variables including catalyst amount, methanol to PFAD mass ratio, and temperature influenced the FFAs conversion. The highest of FFAs of 86.1% was reached at reaction temperature of 65 °C with the PFAD to methanol mass ratio of 4:1, and catalyst amount of 5 wt.% PFAD. The E-R kinetic model as developed can be described the mechanism of esterification reaction